2007
DOI: 10.2174/092986707781368522
|View full text |Cite
|
Sign up to set email alerts
|

Antileukotriene Drugs: Clinical Application, Effectiveness and Safety

Abstract: Cysteinyl leukotrienes (Cys-LTs) are potent proinflammatory mediators derived from arachidonic acid through the 5-lypoxigenase (5-LO) pathway. They exert important pharmacological effects by interaction with at least two different receptors: Cys-LT(1) and Cys-LT(2). By competitive binding to the Cys-LT(1) receptor, leukotriene receptor antagonist drugs such as montelukast, zafirlukast, and pranlukast, block the effects of Cys-LTs and alleviate the symptoms of many chronic diseases, especially bronchial asthma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
102
0
6

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(109 citation statements)
references
References 218 publications
(275 reference statements)
1
102
0
6
Order By: Relevance
“…28 Isolated reports of Churg-Strauss syndrome (CSS), a rare systemic vasculitis asssociated with asthma, have been described in asthma patients treated with montelukast. 29,30 CSS is a rare necrotizing vasculitis with an annual prevalence of approximately 60 per million in asthma patients and 2-7 per million in the general population. 16,31 Its precise etiology is not known, yet its clinical onset is most often preceded by discontinuation or tapering of corticosteroid therapy 26,32 and consists of eosinophilia, pulmonary infiltrates, cardiomyopathy and other signs of vasculitis.…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…28 Isolated reports of Churg-Strauss syndrome (CSS), a rare systemic vasculitis asssociated with asthma, have been described in asthma patients treated with montelukast. 29,30 CSS is a rare necrotizing vasculitis with an annual prevalence of approximately 60 per million in asthma patients and 2-7 per million in the general population. 16,31 Its precise etiology is not known, yet its clinical onset is most often preceded by discontinuation or tapering of corticosteroid therapy 26,32 and consists of eosinophilia, pulmonary infiltrates, cardiomyopathy and other signs of vasculitis.…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
“…16,31 Its precise etiology is not known, yet its clinical onset is most often preceded by discontinuation or tapering of corticosteroid therapy 26,32 and consists of eosinophilia, pulmonary infiltrates, cardiomyopathy and other signs of vasculitis. 29 A likely explanation is that inhaled or oral corticosteroid treatment in these patients may mask the underlying vasculitis that develops as the glucocorticosteroid doses are reduced in patients with severe asthma being treated with leukotriene receptor antagonists (LTRAs). Physicians should be aware of signs and symptoms of CSS in patients with moderate to severe asthma with tapering doses of corticosteroids.…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…They exert important pharmacological effects by interaction with at least two different receptors, CysLT1 and CysLT2 (1,81). By competitive binding to the CysLT1 receptor, leukotriene receptor antagonist drugs such as montelukast, zafirlukast and pranlukast block the effects of cysteinyl leukotrienes.…”
Section: Leukotriene Receptor Antagonistsmentioning
confidence: 99%
“…By competitive binding to the CysLT1 receptor, leukotriene receptor antagonist drugs such as montelukast, zafirlukast and pranlukast block the effects of cysteinyl leukotrienes. Recently published studies and case reports have demonstrated beneficial effects of leukotriene receptor antagonist (LTRAs) on other diseases commonly associated with asthma, e.g., exercise induced asthma, rhinitis, chronic obstructive pulmonary disease, interstitial lung disease, chronic urticaria, atopic dermatitis, allergic fungal disease, nasal polyposis, and paranasal sinus disease (81). LTRAs are not licensed for urticaria.…”
Section: Leukotriene Receptor Antagonistsmentioning
confidence: 99%